Mercury Removal from Actual Petroleum Based Industries Wastewater by P. putida in Membrane Bioreactor - Abdul Aziz, Mohd Azoddein; R. A., Bakar; Nik Meriam, Nik Sulaiman; Ahmad Bazli, Bustary; Nur Athirah, Mohamad Basir (2015)
Mercury is an extremely toxic pollutant that currently being emitted and distributed globally. Several petroleum based industrial plants had showed high concentration of mercury compare to the Department of Environmental (DOE), Malaysia. Microbes have been used to solve environmental wastewater problems for many years. Objective of this study is to remove mercury from actual petrochemical wastewater using Pseudomonas putida (P. putida), in membrane bioreactor. To achieve the maximum of mercury removal, the optimum growth parameters of P. putida were obtained. Based on the optimum parameters of P. putida for specific growth rate, µ the removal of 4 mg/L was studied. Results showed mercury removal for sample with 4 mg/L mercury in bioreactor is 99.60% for the first 6 hours, 99.80% removal for 120 hours and 99.90 % after the microfiltration membrane system. The specific growth rate (μ) describes how fast the cells are reproducing. The higher the value of specific growth rate, then the faster the cells are growing.In this case, 6 hours was the optimum time for the mercury removal with the ratio of mercury mass over cell mass is 20.78 µgHg/g cells for P. putida. Microfiltration membrane enhanced further the treatment of the wastewater by retaining the P. putida from escaping during the release of treated wastewater, reducing the turbidity by 94.2% (5.32 NTU) and concentration of suspended solids up to 60.4% (0.09 mg/L). The mechanism of mercury detoxification in the membrane bioreactor was based on reduction of Hg²⁺ to non-toxic Hg0 by mercury reductase enzyme produced by P. putida. The findings from this study can be used as references for future application of petroleum based industries wastewater treatment as well as other industries related to mercury contamination in their wastewater treatment plant such as gold mining, chemical industries, agriculture etc.